I need an help with the following exercise. I've already seen this question Prove that Brownian Motion absorbed at the origin is Markov but I don't understand the answer. Also I would like to prove the thing differently (at least the two ways seem different to me).

So let $\tau$ be the first time the Brownian motion arrives in $0$ and define

$W^x_t = \begin{cases} x+B_t &\mbox{if } t\leq \tau \\ 0& \mbox{else }. \end{cases} $

Here we denote with $B_t$ the standard Brownian motion starting at $0$ and with $B_t^x$ the Brownian motion starting at $x$, so $B_t^x=x+B_t$.

I want to compute the transition function for the process, i.e. $p(t,x,A)$.

I've already got an hint: show that $\mathbb P(B_t^x\in A)= \mathbb P(B^x_t\in A,B_s^x>0 \,\forall s \in [0,t] )+\mathbb P(B_t^x\in -A)$, for each $x>0, A\subset (0+\infty).$

Now I see that if I prove the hint, I'm done, but I don't know how to prove the hint. I know that I should use reflection principle, but how? Any help will be really appreciated.

  • $\begingroup$ As far as I can tell, the claimed identity does not hold true. $\endgroup$ – saz May 9 '15 at 15:25
  • $\begingroup$ Have you solved that question? or are you still looking for some ideas? $\endgroup$ – Conrado Costa Jul 24 '15 at 16:26

$$\mathbb{P}(B^x_t\in A)=\mathbb{P}(B^x_t\in A,B^x_s>0,\forall s\in [0,t])+\mathbb{P}(B^x_\tau=0,B^x_t\in A)$$ where $$\tau=inf\{s,B^x_s=0,s\in[0,t]\}$$ And $$\mathbb{P}(B^x_\tau=0,B^x_t\in A)=\mathbb{P}(B^x_\tau=0,B^x_t\in -A)=\mathbb{P}(B^x_t\in -A)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.